First record of Greenidea psidii van der Goot and comparison with Greenidea ficicola Takahashi (Hemiptera: Aphididae) in Brazil - Lazzari, Sonia Maria Noemberg; Zonta-De-Carvalho, Regina Célia; Cardoso, Josiane Teresinha; Calado, Daniéla Cristina (Zootaxa, 2006)
Greenidea psidii van der Goot, 1916 is registered by the first time in Brazil. It was found associated with Psidium guajava L. in Paraná, Santa Catarina, and São Paulo States, and with Psidium cattleianum Sabine in the city of Curitiba, Paraná. A brief comparative synopsis and pictures of the main diagnostic characters are given for this species and for Greenidea ficicola Takahashi, 1921, which was also recently found in Brazil, collected on Ficus benjamina (L.) in Paraná and Santa Catarina, and on Ficus microcarpa L. in São Paulo State.